Nyadran Ngayung Budaya Lokal dalam Mewujudkan Harmoni dan Toleransi Beragama - Fahimah, Siti; Syarifah, Umaiyatus (Proceedings of Annual Conference for Muslim Scholars, 2024)
The focus of this research is Nyadran tradition in Ngayung Lamongan, and the way how Islamic values can be integrated with local wisdom to create harmony and tolerance in a multicultural society. Over the years, Nyadran has become a symbol of solidarity and harmony between religious communities as a local cultural and religious ritual. This tradition does not only show the close relationship between humans and nature, but also shows the values upheld by Islam. This research explores the symbolic meaning of each Nyadran ritual and the way how Islam is implemented. This research uses qualitative research with ethnographic approach. The results of this research show that Nyadran plays an important role in strengthening brotherhood between religious communities, creating opportunities to maintain harmonization of various cultures and encouraging the values of tolerance. By incorporating Islamic values into local wisdom, such as Nyadran, it can help strengthening a harmonious and tolerant social order in society. This tradition does not only help maintaining local wisdom, but also helps spreading the message of tolerant religion